The Effect of Debt To Asset Ratio, Debt To Equity Ratio To Nett Profit Margin (Case Study of PT Waskita Karya (Persero) Tbk In 2018-2022) - Muhammad Distian Andi Hermawan (Sinergi International Journal of Accounting and Taxation, 2023)
The purpose of this study is to see and determine the effect between debt asset ratio and debt equity ratio on net profit margin both partially and simultaneously. This research is a quantitative research with secondary data obtained from the Indonesia Stock Exchange, in the period 2018-2022. Sample selection, the method used is purposive sampling, Data collection techniques used in this study are secondary data, data analysis techniques using the SPSS Version 24 statistical program. The test results are partially obtained, namely: The variable Debt to Asset Ratio (X1) does not have a partially significant effect on Net profit Margin (Y) because the significance level value is greater than 0.005. The variable Debt to Equity Ratio (X2) has a significant effect partially because the significant value is smaller than 0.005, the test results simultaneously obtained the result of the significance value of 0.034 which is smaller than 0.005, it can be concluded that both variables Debt to Asset Ratio (X1) and Variable Debt to Equity Ratio (X2) have a positive and significant influence on the dependent variable, namely Nett profit Margin (Y)